A Systematic Review and Meta-Analysis of Efficacy, Cost-Effectiveness, and Safety of Selected Complementary and Alternative Medicine for Neck and Low-Back Pain. (24th November 2011) - Furlan, Andrea D.; Yazdi, Fatemeh; Tsertsvadze, Alexander; Gross, Anita; Van Tulder, Maurits; Santaguida, Lina; Gagnier, Joel; Ammendolia, Carlo; Dryden, Trish; Doucette, Steve; Skidmore, Becky; Daniel, Raymond; et al.
Abstract : Background . Back pain is a common problem and a major cause of disability and health care utilization. Purpose . To evaluate the efficacy, harms, and costs of the most common CAM treatments (acupuncture, massage, spinal manipulation, and mobilization) for neck/low-back pain. Data Sources . Records without language restriction from various databases up to February 2010. Data Extraction . The efficacy outcomes of interest were pain intensity and disability. Data Synthesis . Reports of 147 randomized trials and 5 nonrandomized studies were included. CAM treatments were more effective in reducing pain and disability compared to no treatment, physical therapy (exercise and/or electrotherapy) or usual care immediately or at short-term follow-up. Trials that applied sham-acupuncture tended towards statistically nonsignificant results. In several studies, acupuncture caused bleeding on the site of application, and manipulation and massage caused pain episodes of mild and transient nature. Conclusions . CAM treatments were significantly more efficacious than no treatment, placebo, physical therapy, or usual care in reducing pain immediately or at short-term after treatment. CAM therapies did not significantly reduce disability compared to sham. None of the CAM treatments was shown systematically as superior to one another. More efforts are needed to improve the conduct and reporting of studies of CAM treatments.